Perilaku Inovatif Guru Melalui Kepemimpinan Transformasional, Knowledge Sharing, dan Kompetensi Digital - Purwanto, Anim; Suryadi, Suryadi; Nursofah, Nursofah; Istiqomah, Istiqomah (Indo-MathEdu Intellectuals Journal, 2024)
This study focuses on the problem of low innovative behavior of teachers that can hinder effective learning processes. The purpose of this study was to analyze the influence of transformational leadership, knowledge sharing, and digital competence on innovative behavior of teachers. The research method used was quantitative involving a sample of 143 teachers at the Nurul Iman Islamic Boarding School in Bogor. Data collection technique used an instrument with a Likert scale distributed to respondents, while inferential statistics were used to analyze the data. The results showed that there was a significant positive effect between transformational leadership and innovative behavior of teachers, where support and motivation from educational leaders contributed to increased creativity and innovation in teaching. In addition, knowledge sharing was shown to increase collaboration between teachers, while digital competence facilitated the application of technology in more innovative learning. The implications of these findings emphasize the importance of developing inspirational leadership and improving  teachers' digital skills to create a more dynamic and responsive learning environment to students' needs. Thus, schools need to design training programs that focus on these aspects to support teacher professional development and improve the quality of education